Determinants of an integrated management of childhood illness program implementation in Indonesia - Amalia, Dwi Octa; Hadi, Ella Nurlaella (BKM Public Health and Community Medicine, 2023)
Purpose: This study aims to identify the factors related to health system support that influence the implementation of Integrated Management of Childhood Illness (IMCI) in primary health care facilities in Indonesia, specifically in relation to leadership. Methods: The research method used is a literature review. Database searches of Garuda, Google Scholar, Proquest, Science Direct, Biomed, and Pubmed were performed from 2012 to 2022 using the keywords “manajemen terpadu balita sakit”, “IMCI Indonesia”. Results: A total of 1,238 articles were screened for eligibility and five published articles met the inclusion criteria and objectives of this literature review. Based on five articles reviewed, nine variables associated with IMCI implementation were analyzed in this study, including leadership support, supervision, completeness of medicine and medical equipment, presence of consultation room, motivation, attitudes, knowledge, and completeness of filling out forms. Conclusion: The support of the health system is a key challenge in implementing IMCI. Therefore, strengthening health system support is needed to optimize the implementation of IMCI. In addition, there is a need to strengthen leadership and provide regular supervision and feedback to ensure that IMCI implementation is in accordance with standards and to increase health worker motivation to improve their performance in providing health services.